IMPLEMENTASI PENDEKATAN KONTEKSTUAL DALAM PEMBELAJARAN BAHASA JAWA - -, Suwarna (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2006)
Knowledge is not a set of facts, concepts, or methods taken readily,memorized, or remembered. Human beings have to construct it and give itmeaning through real experience. This is the philosophy on which thedevelopment of the contextual approach to teaching and learning is based (thougha more well-known term is contextual teaching and learning or CTL).The approach mentioned above is appropriate for language study becausein learning language the learner always has interactions with the context of thelanguage and continuously constructs the science and experience obtained. Thenthe learner applies the science and experience in real life so that they have ameaning in life.The implementation of the contextual approach in learning Javaneseconsists of (1) the formulation of purposes, (2) the formulation of the steps orscenario of the teaching and learning, (3) the use of media, (4) authenticassessment, and (5) reflection.Keywords: construct, real life, implementation, contextual approach